Edukasi Penggunaan Sunscreen dalam Kehidupan Sehari-Hari di SMK Farmasi Al-Furqon Banjarmasin - Mi'rajunnisa, Mi'rajunnisa; Khoirul Usmanul Hakim; Mala Arianti; Siti Putri Juliana (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Sunscreen is a cosmetic was used with the aim of actively reflecting or absorbing sunlight, especially in areas with ultraviolet and infrared wave emissions, so as to prevent skin disorders due to UV rays. This educational activity aims to describe students' knowledge regarding the importance of using sunscreen to prevent skin cancer at Al-Furqon Vocational School, Banjarmasin Utara, Banjarmasin City, South Kalimantan. The activity was carried out using the socialization method using Power Point Presentation (PPT) and leaflets to present material related to the importance of using sunscreen and how to use it.  a questionnaire was used after giving the material to measure the level of knowledge of the students, Based on the pre-test results, only 15 out of 17 students answered the questions correctly, then the post-test results showed that 17 students answered all the questions correctly. Community Service Activities in the context of providing information and education to vocational school students about the use of sunscreen to prevent skin cancer have been carried out well and have increased students' knowledge regarding the importance of using sunscreen in everyday life.